The Roles of Teachers’ Work Motivation and Teachers’ Job Satisfaction in the Organizational Commitment in Extraordinary Schools - Fatwa Tentama; Dessy Pranungsari (International Journal of Evaluation and Research in Education (IJERE), 2016)
Teachers’ work motivation and teachers’ job satisfaction are the factors influencing the organizational commitment. This research is aimed to empirically examine the roles of teachers’ work motivation and teachers’ job satisfaction in the commitment of the organization in extraordinary schools. The subjects of the research are the teachers in Extraordinary School 1 Bantul Yogyakarta. The sample was taken by employing non-randomized technique. The scales of work motivation, job satisfaction and organizational commitment are used in collecting the data. The data were analyzed by using multiple linear regression technique. The results of the research show that 1) simultaneously, teachers’ work motivation and teachers’ job satisfaction are highly significant positive correlated with organizational commitment, by reaching the score of Rx1x2v=0,621 with the probability p=0,002 (p<0,01); 2) teachers’ work motivation are highly significant correlated with the organizational commitment, by reaching the score of (rx1v))=0,614 and the probability p=0,000 (p<0,01); 3) teachers’ job satisfaction is highly significant positive correlated with organizational commitment, by reaching the score of (rx2v))=0,570 and probability p=0,001 (p<0,01). Teachers’ job motivation more dominantly influence organizational commitment compared to teachers’ job satisfaction